Enhancing 10th Grade Senior High School Students Reading Skills Using Popular Folklore in Indonesia - Dinda Rahmah Az zahrah; Nur Fauzia (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
Reading is a process in which the reader tries to understand the meaning that the writer wants to convey through written language. Good reading skills have a great effect on improving students' academic achievement, while difficulties in understanding reading can be an obstacle in the learning process. Therefore, teachers have an important role in encouraging students to use reading materials that are appropriate, interesting, and relevant to the subject matter. One form of reading material that can be used is folklore. Reading folklore in the classroom not only introduces students to the richness of local culture, but it can also increase their excitement, interest, and engagement in reading activities. This study aims to evaluate the significance of differences in students' reading comprehension scores before and after the introduction of Indonesian folklore as reading material. This study used a pre-experimental design involving 35 students of class X in one of the Senior High Schools (SMA) in Gresik. The data collection procedure is carried out in three stages, namely pre-test, treatment, and post-test. The results of the study showed a significant increase in the value of students' reading comprehension. The average score of the students' pre-test was 60.71 and increased to 85 on the post-test. In addition, the percentage of students who achieved learning completeness also increased from 48.57% to 91.43%. These findings indicate that the use of folklore as a teaching material in reading learning can have a positive impact on student understanding. Therefore, it is recommended that teachers consider the use of folklore as an alternative reading material in Indonesian learning to improve reading skills effectively and funly.